Prevalence of diseases of pigeons and responses to treatment of bacterial disease (Bangladesh Veterinarian, 2022)
The prevalence of diseases of pigeon and response to treatment of bacterial disease were studied. One thousand pigeons were collected and examined to diagnose diseases following clinical history and signs, post-mortem lesions and laboratory examination. The overall prevalence of pigeon diseases was 21.9% (n = 219). Parasitic infestation was significantly (P